Phosphorus Sorption Pattern Under Controlled Redox Potential For Crowley Silt Loam Soil - Husin, Alias (1982)
Four samples of Crowley silt loam soil were weighed into a 2-liter flat-bottomed flasks. After the introduction of 0.4% ground rice straw, 0.01 M CaCl2 were added in each flask and the mixture stirred constantly by a magnetic stirrer to establish oxidized and reduced conditions. It took 13 days of continuous purging with nitrogen gas to obtain an Eh value of -220 mv. For the oxidized condition ordinary atmospheric air was bubbled into the flasks. Two levels of P (10 ppm and 100 ppm) in the form of Ca(H2P04)2H2 0 was applied to the soil mixture. It was found that the pH of the aerated treatment remained rather constant throughout the entire investigation whereas in the reduced ones the pH increased from 5.5 to neutrality. More P was adsorbed under the reduced condition than the oxidized ones. However, the effect was much more pronounced at the higher level of P fertilization. After 288 hours there were 55.9% and 90.2% adsorption of P in the oxidized and reduced conditions respectively. For 10 ppm P the maximum adsorption was obtained after a two-day period whereas for 100 ppm P. The graph levelled off after six days.